Unnatural habitat: Redesigning spaces for support of biodiversity and bring a human & nature coexistence - Kuklinska, Aleksandra (My University, 2023)
Sustainability becomes an inseparable element of the built environment. We observe that the most popularized sustainable solutions are focusing mostly on aspects of building materials or energy efficient systems. However, even building in a new environmentally-friendly way, still interferes in natural habitat and leads to its slower or faster degradation. There is a gap of building examples that would consider biodiversity support in the early stage of the project. At the same time, it is already well-known that nature has a big positive impact on our mental health and well-being. How beneficial would it be then, for both of the sides (human - nature) if architects started to design spaces with inclusion of wildlife in the built environment? The purpose of the work is to draw attention to the problem of exclusion of biodiversity in the field of architecture and habitat degradation caused by ongoing urbanisation. In order to achieve a coexistence between human and nature, newly designed projects, as well as already existing spaces should aim to integrate nature in the built environment. The aim of this thesis is however to highlight the importance of transformation and redesign of already existing outdoor spaces. The research part was based on literature and study of references to ground a base of present knowledge. In the next stage, the context of the site was analysed in order to get a bigger picture and understand wider correlations between chosen site and other biodiversity valuable areas. Later, the process of rethinking and redesigning were made in relation to stated findings and was summarised with sketch concepts for ideas of adjustments. The final proposal is a presentation of a few selected concepts, shown with drawings and perspectives. This paper does not provide a biological knowledge about biodiversity but is taking an architectural perspective as a main direction. Thesis illustrates how big possibilities can be found in already existing spaces and how crucial the transformation approach can be for the prevention of biodiversity loss. The results show that the broader local context and cross-disciplinary approach is needed for achieving a new healthy shared habitat.
Keywords: Biodiversity support; Shared habitat; Human-nature